2013
DOI: 10.4103/2152-7806.123783
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic cerebrospinal fluid pseudocyst: A rare complication of ventriculoperitoneal shunt

Abstract: Background:Ventriculoperitoneal (VP) shunts are among the most frequently performed operations in the management of hydrocephalus. Hepatic cerebrospinal fluid (CSF) pseudocyst is a rare but important complication in patients with a VP shunt insertion. In addition to presenting our own case, we performed a PubMed search to comprehensively illustrate the predisposing factors, clinical picture, diagnostic methods, and surgical treatment. This article represents an update for this condition.Case Description:A 40-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 28 publications
3
27
0
Order By: Relevance
“…In literature, it is seen that laparoscopy procedures are favored in the recent years [10]. In the presence of an infection, it is suggested that implanting an external ventricular drain and installing a new shunt after appropriate antibiotherapy and seeing CSF is sterile [2,4,8]. In our cases we saw that, sending the catheter to a different quadrant, without excision of the pseudocysts, is sufficient.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…In literature, it is seen that laparoscopy procedures are favored in the recent years [10]. In the presence of an infection, it is suggested that implanting an external ventricular drain and installing a new shunt after appropriate antibiotherapy and seeing CSF is sterile [2,4,8]. In our cases we saw that, sending the catheter to a different quadrant, without excision of the pseudocysts, is sufficient.…”
Section: Discussionsupporting
confidence: 50%
“…In pediatric patients, abdominal pseudocysts are mostly presented with the symptoms caused by the elevated intracranial pressure; on the other hand, adult patients are usually presented with abdominal symptoms. There are also cases presented with both symptoms, as ours [2,8]. Main pathologies in differential diagnosis with abdominal pseudocysts are mesenteric or omental cysts, duplication cysts, Iymphocele, cystic teratoma, cystic lymphangioma, pancreatic pseudocyts, abscess and bilomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pathogenesis of CSF pseudocyst is at least in part related to the prior abdominal surgery and liver dysfunction [9], as well as infections and allergic reactions to silicone or ethylene oxide [10]. Potential organisms that are implicated in CSF pseudocysts include Staphylococcus epidermidis, Staphylococcus aureus, and Propionibacterium acnes [11]. In the present case, no microorganism growth was observed in the cultures of the cyst fluid and the distal shunt tip.…”
Section: Discussionmentioning
confidence: 83%